(untitled) (Research, Society and Development, 2020)
Today’s society has demanded critical individuals capable of carrying out collaborative practices and being able to find answers relevant to different situations, thus requiring a more dynamic teaching in which students are the subject of their learning process and how the teaching of Mathematics suffers rejection by many students due to different reasons, it is relevant that the teacher rethink his methodological practice. The objective of the present work is to present the results of a state-of-the-art research on the active methodology in the teaching of mathematics. To this end, a research was carried out with a qualitative approach classified as exploratory and used the bibliographic research method called Systematic Literature Review (RSL). The research took place in the CAPES Periódicos Portal Database that, after searching, selecting and analyzing the articles in the last ten years, five articles were selected that made it possible to view the panorama of this theme. The analysis undertaken pointed out that the use of Active Methodologies as a strategy for the teaching of Mathematics stimulates knowledge, encourages reflections and challenges students to solve problems.